E-learning as an Effective Method in the Prevention of Patient Falls - Horová, Jana; Brabcová, Iva; Bejvančická, Petra (Zdravstveno varstvo, 2021)
Objectives: Patient falls deteriorate patients' functional condition and quality of life, and increase their treatment costs. E-learning is considered an effective way to gain knowledge and competencies for quality and safety in nursing practice. The aim of the study is to evaluate the effectiveness of an e-learning course for nurses in preventing in-patient falls. Methods: The research design was mixed. In the first phase of the study, a five-year retrospective analysis of 2,280 in-patient falls was performed. Based on the analysis of risk factors for patient falls and group interviews with clinic managers an e-learning course was designed and completed by 250 nurses from five surgical and internal departments. The course's effectiveness was evaluated based on the incidence of patient falls and the consequences of the falls before and after e-learning. Results: At surgical departments, there was a statistically significant decrease in patient fall indices after the implementation of the e-learning course (from 4.4 to 2.6 falls per 1,000 patients; p=0.022). On the contrary, in internal departments, this index increased in the monitored period (from 19.0 to 26.9 falls per 1,000 patients; p=0.001). In all departments, there was a decrease in the incidence of patient injuries caused by falls after the implementation of the e-learning course; in internal medicine, this decrease was statistically significant (from 54.5% to 33.3%; p=0.014). Conclusions: The study confirmed that e-learning forms of education for healthcare professionals have a positive effect in preventing patient falls.